Disruption of the endopeptidase ADAM10-Notch signaling axis leads to skin dysbiosis and innate lymphoid cell-mediated hair follicle destruction - Sakamoto, Keiko; Jin, Seon-Pil; Goel, Shubham; Jo, Jay-Hyun; Voisin, Benjamin; Kim, Doyoung; Nadella, Vinod; Liang, Hai; Kobayashi, Tetsuro; Huang, Xin; Deming, Clay; Horiuchi, Keisuke; et al. (Immunity (Cambridge, Mass.), 2021)
Hair follicles (HFs) function as hubs for stem cells, immune cells, and commensal microbes, which must be tightly regulated during homeostasis and transient inflammation. Here we found that transmembrane endopeptidase ADAM10 expression in upper HFs was crucial for regulating the skin microbiota and protecting HFs and their stem cell niche from inflammatory destruction. Ablation of the ADAM10-Notch signaling axis impaired the innate epithelial barrier and enabled Corynebacterium species to predominate the microbiome. Dysbiosis triggered group 2 innate lymphoid cell-mediated inflammation in an interleukin-7 (IL-7) receptor-, S1P receptor 1-, and CCR6-dependent manner, leading to pyroptotic cell death of HFs and irreversible alopecia. Double-stranded RNA-induced ablation models indicated that the ADAM10-Notch signaling axis bolsters epithelial innate immunity by promoting β-defensin-6 expression downstream of type I interferon responses. Thus, ADAM10-Notch signaling axis-mediated regulation of host-microbial symbiosis crucially protects HFs from inflammatory destruction, which has implications for strategies to sustain tissue integrity during chronic inflammation.